Direct laser deposition of nanostructured tungsten oxide for sensing applications. (15th April 2016) - Palla-Papavlu, Alexandra; Filipescu, Mihaela; Schneider, Christof W; Antohe, Stefan; Ossi, Paolo M; Radnóczi, György; Dinescu, Maria; Wokaun, Alexander; Lippert, Thomas
Abstract: Nanostructured tungsten trioxide (WO3 ) thin films are deposited by pulsed laser deposition (PLD) and radio-frequency (RF) assisted PLD onto interdigitated sensor structures. Structural characterization by x-ray diffraction and Raman spectroscopy shows the WO3 films are polycrystalline, with a pure monoclinic phase for the PLD grown films. The as-fabricated WO3 sensors are tested for ammonia (NH3 ) detection, by measuring the electrical response to NH3 at different temperatures. Sensors based on WO3 deposited by RF-PLD do not show any response to NH3 . In contrast, sensors fabricated by PLD operating at 100 °C and 200 °C show a slow recovery time whilst at 300 °C, these sensors are highly sensitive in the low ppm range with a recovery time in the range of a few seconds. The microstructure of the films is suggested to explain their excellent electrical response. Columnar WO3 thin films are obtained by both deposition methods. However, the WO3 films grown by PLD are porous, (which may allow NH3 molecules to diffuse through the film) whereas RF-PLD films are dense. Our results highlight that WO3 thin films deposited by PLD can be applied for the fabrication of gas sensors with a performance level required for industrial applications.